Differences in below-ground bud bank density and composition along a climatic gradient in the temperate steppe of northern China. (14th June 2017) - Qian, Jianqiang; Wang, Zhengwen; Klimešová, Jitka; Lü, Xiaotao; Kuang, Wennong; Liu, Zhimin; Han, Xingguo
Abstract: Background and Aims Understanding the changes in below-ground bud bank density and composition along a climatic gradient is essential for the exploration of species distribution pattern and vegetation composition in response to climatic changes. Nevertheless, investigations on bud banks along climatic gradients are still scarce. The below-ground bud bank is expected to be reduced in size in arid conditions, and costly, bud-bearing organs with long spacers would be replaced by more compact forms with buds that are better protected than those found in moist conditions. Methods How total bud density and composition (different bud bank types) change with aridity (calculated value 0·43–0·91), mean annual precipitation (MAP; 93–420 mm) and mean annual temperature (MAT; −1·51 to 6·93 °C) was tested at 21 sites along a 2500-km climatic gradient in the temperate steppe of northern China. Key Results The relationship between below-ground bud bank density and precipitation/aridity was fundamentally changed along the climatic gradient. Bud bank density increased first and then decreased along the aridity and MAP gradients, the turning points being aridity=0·67 and MAP=260 mm, respectively, while it decreased consistently with increasing MAT. The proportion of the bud bank that comprised tiller buds or dicotyledonous herb buds fluctuated along the aridity gradient. The proportion of rhizome buds was higher at relatively moist sites (aridity <0·75), while that of bulb buds was higher at drier sites (aridity >0·75). Conclusions Belowground bud bank density decreases towards the dry, hot end of the climatic gradient. Based on the distribution of bud types along the climatic gradient, bulb buds and tiller buds of tussock grasses seem to be more resistant to environmental stress than rhizome buds. The dominance of annual species and smaller bud banks in arid region implies that plant reproductive strategies and vegetation composition will be shifted in scenarios of increased drought under future climate change.